Empowering communities for malaria control: Effectiveness of community-led biolarviciding using Bacillus thuringiensis israelensis in The Gambia - Babucarr Jassey; Ririh Yudhastuti; Buba Manjang; Ibrahim Touray; Muhammad Rasyid Ridha; Khuliyah Candraning Diyanah; Fitiara Indah Permatasari (Veterinary World)
Background and Aim: In The Gambia, malaria transmission persists due to insecticide resistance and residual vector behavior, despite extensive use of indoor residual spraying and insecticide-treated nets. Community-led larval source management using Bacillus thuringiensis var. israelensis (Bti) offers a sustainable vector control alternative. This study aimed to assess the effectiveness and feasibility of community-led Bti application for reducing Anopheles mosquito populations, compared to expert-supervised application and non-intervention control arms.